Reconstructing the Legal Understanding of the Presumption of Innocence in Criminal Justice to Achieve Justice - Heri Purwanto; Pujiyono; Irma Cahyaningtyas; Ridwan Arifin; Muhammad Azil Maskur (Indonesian Journal of Criminal Law Studies, 2025)
The presumption of innocence (APTB) is a well-known principle that guarantees human rights. This principle is also used in criminal law to protect suspected criminals. The problem is that law enforcement officials do not fully understand this principle in criminal proceedings, as they tend to believe that the presumption of guilt applies to suspected criminals. Law enforcement officials believe that the judicial process cannot proceed if the presumption of guilt principle is not applied. However, the APTB is not the opposite of the presumption of guilt principle; rather, it is a principle that can bring balance to the criminal justice process by prioritizing legal protection for those seeking justice to prevent them from facing arbitrary actions by law enforcement officials. This method employs normative research, prioritising the analysis of secondary data/literature supported by other literature and cases drawn from internet sources. The findings of this study explain that law enforcement officials' understanding of APTB is crucial in the criminal justice process as a form of legal protection for those seeking justice. Applying the principle must be supported by clearly incorporating APTB into the provisions of the Criminal Procedure Code (KUHAP) for the future. Currently, APTB is not regulated in the provisions of the KUHAP, so in the future, when the principle is regulated, law enforcement officials in the criminal justice process will have a strong basis for not disregarding the presumption of innocence principle.